La interculturalidad del español: corrección y adecuación de saludos y direcciones en la evaluación de profesores nativos - Ainciburu, María Cecilia; Velasco, David Rodríguez (Studia Romanica Posnaniensia, 2021)
This research aims to investigate the presence in textbooks of varied material in terms of geolectal equivalents and its perception by teachers of Spanish as a foreign language. In order to examine potential differences in their approach, a pedagogical framework-based task was designed to study a corpus of 100 ELE teachers’ evaluations (50 from Colombia and 50 from Spain) and examine their consciousness and dissimilarities regarding pragmatic correctness when expressing addresses and greeting headings in electronic messages. The results show that native teachers tend to consider as correct the stimuli of peninsular Spanish or of their own variety, while those representing different geolectal variations of Spanish tend to score very low, even being considered as inter or intralinguistic error.